STUDI PENYETELAN RELAI DIFERENSIAL PADA TRANSFORMATOR PT CHEVRON PACIFIC INDONESIA - Liem Ek Bien, Liem Ek Bien; Helna, Dita (Jurnal Teknik Elektro, 2007)
The quality of an electric power system is measured by its continuity of service, good controland maintenance. The good continuity of service can be obtained if all the components ofpower systems can operate well in every situation and condition, either in normal or inabnormal condition. In abnormal condition, the protection system has an important role indetecting every disturbance and disconnecting the disturbed parts from the system. Thepower transformer is the main component in a substation. The disturbances in thetransformer should be isolated so as not to disturb the system during distribution of theelectric power to other load. The differential relay on the power transformer is a protectionrelay to detect internal disturbance. This paper discusses the setting and mismatch error ofdifferential relay in substation of Central Duri at switchgear #3 at PT Chevron PacificIndonesia (PT CPI).Keywords: short circuit, differential relay, power transformer